HUBUNGAN USIA DAN PARITAS DENGAN KEJADIAN ANEMIA PADA IBU HAMIL DI PUSKESMAS SERANG KOTA TAHUN 2024 - Muhida, Vega (Journal of Health Service Management, 2026)
Background: Maternal anemia remains a major public health problem and contributes to adverse pregnancy outcomes. Factors such as maternal age and parity are known to influence the risk of anemia during pregnancy. Objective: To analyze the relationship between maternal age and parity with the incidence of anemia among pregnant women in Serang City Health Center Methods: This quantitative analytic study used secondary data from the laboratory register of pregnant women recorded between January–December 2024. A total of 290 samples were selected using systematic sampling. Variables included hemoglobin level, maternal age, and parity. Data were analyzed using univariate and bivariate analysis (chi-square test and odds Results: The prevalence of anemia was 22%. Pregnant women with risky age (<20 or >35 years) were more likely to be anemic (52.1%). Chi-square test showed a significant association between age and anemia (p < 0.001), with OR = 7.56. Risky parity (primipara & grande multipara) was also associated with anemia (52.8%) with significant results (p < 0.001), OR = 8.25. Conclusions: Maternal age and parity are significantly associated with anemia among pregnant women. Strengthened screening and targeted education are needed especially for high-risk groups.